Numerical investigation of flow structures resulting from the interaction between an oblique detonation wave and an upper expansion corner. (25th November 2020) - Wang, Kuanliang; Teng, Honghui; Yang, Pengfei; Ng, Hoi Dick
Abstract: Abstract : Wedge-induced oblique detonation waves (ODWs) have been studied widely, but their interactions with complicated geometries have not been fully addressed. In this study, we investigate ODW interaction with a deflected upper corner due to confinement change upstream of the ODW. Numerical simulations are conducted using the reactive Euler equations with a two-step induction–reaction kinetic model. Two ODWs without the upper wall deflection are first simulated to resolve the basic structures with inflow Mach numbers $M_0 = 6$ and 7. Thereafter, we introduce a deflected upper confinement, resulting in a new wave configuration. This wave is characterized by a post-turning, triangular recirculation zone coupled with a gaseous wedge connecting the deflection point and ODW surface. A parametric study is performed to analyse the effects of the deflection location, deflection angle and activation energy of the heat release reaction. The results reveal that the wave configuration is due to the evolution of ODW decoupling in an expanded supersonic flow. We further study the surface stability and structural unsteadiness arising for $M_0 = 6$ . Upstream-travelling transverse waves are observed for the first time, and effects of different parameters on the surface instability are analysed via fast Fourier transforms. Two destabilizing mechanisms of ODW structures are proposed, one from the post-surface thermal choking and the other from the enhanced surface instability.